Uncover a Dolphin : Uncover books - Gordon, David George (San Diego : Silver Books, 2008)
Did you know that dolphins drink milk? Or that some scientists believe dolphins' ancestors once walked on land? Today, there are 37 different kinds of dolphins, from the familiar bottlenose to some rare river-dwellers. Uncover the secrets of dolphins, layer by layer, in this unique book. Kids can plunge into weird and wild facts, cool illustrations, diagrams, and an amazing 3-D layered model of a bottlenose dolphin. With over 4 million copies in print, the Uncover It series combines the best elements of a book with 3-D layered models to help readers truly "uncover" the mysteries of what makes things work, providing a unique approach to learning. The series' three-dimensional presentation allows for in-depth exploration of each subject. Each title features colourful illustrations and a unique "model" that can be built and deconstructed, layer by layer, by simply turning the page. Ages 8 and up
Keywords: Anatomy -- Animals -- Board book